Assessing response styles to positive affect: One or two dimensions of positive rumination in the Responses to Positive Affect questionnaire?. (January 2016) - Nelis, Sabine; Luyckx, Koen; Feldman, Greg; Bastin, Margot; Raes, Filip; Bijttebier, Patricia
Abstract: The Responses to Positive Affect questionnaire (RPA) assesses responses that either tend to dampen or enhance positive affect. Previously, using factor analysis, enhancing (i.e., positive rumination, PR) has been divided into self-focused and emotion-focused strategies. Whereas these PR types are mostly treated as different factors, they are also examined as a single factor, for instance in adolescents. Given that self-concept changes through adolescence, there might be an age effect such that self-focused PR and emotion-focused PR become more differentiated through adolescence. The present aim was to investigate the distinction between emotion-focused and self-focused PR by comparing the RPA structure in three age groups, i.e., early, middle, and late adolescence (Study 1); and by conducting a systematic review of the relationship between both strategies in published research (Study 2). In Study 1, we found no evidence that the two types of PR were more differentiated in the oldest than in the youngest group. In Study 2, related to Study 1, self-focused and emotion-focused PR were highly correlated in most of the published research. Also, there were item switches between the PR factors in RPA translations. In sum, it is justifiable to investigate PR as a single construct when using the RPA. Highlights: The RPA assesses responses to positive affect: positive rumination (PR) and dampening. We examined the distinction between two types of PR in the RPA. We incorporated new data in adolescents and data from published papers. The two types of PR were not more differentiated at late than at early adolescence. PR can be treated as a single construct when using the RPA.